Tari Pecut dalam Tradisi Karapan Sapi: Representasi Budaya Madura - Puspitasari, Desi; Saksono, Suryo Tri (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2025)
Tari Pecut is a traditional dance that is part of the Karapan Sapi performing arts in Madura Island. This dance symbolizes courage, warrior spirit, and the uniqueness of Madurese culture. This study aims to explore the symbolic meanings of costumes and props in Tari Pecut and analyze how the dance represents Madurese culture using Charles Sanders Peirce’s semiotic approach. Employing a descriptive qualitative method, data were collected through observation, interviews, and documentation, then analyzed based on the concepts of sign, object, and interpretant. The findings are expected to provide a deeper understanding of Tari Pecut as a manifestation of Madurese culture and reveal the values, norms, and cultural experiences embedded in its elements.